Strategi Literasi Anak Berbasis Sastra dalam Pengembangan Nilai Interkultural - Umamy, Etty; Kustyarini (Adjektiva: Educational Languages and Literature Studies, 2025)
In the era of globalization, education plays a crucial role in instilling intercultural values in children; however, the lack of systematic approaches remains a major challenge. This study aims to formulate effective literature-based literacy strategies for developing intercultural values, evaluate their impact, and identify challenges and opportunities in their implementation. Using a qualitative approach with a case study method, this research analyzes the implementation of literature-based literacy strategies through semi-structured interviews, classroom observations, document analysis, and questionnaires involving students, teachers, and literary materials used in learning. The findings indicate that this strategy is effective in enhancing students' understanding and appreciation of cultural diversity, improving social interactions, and fostering empathy toward different cultural perspectives. The analysis of questionnaire data using a Likert scale reveals a significant increase in students’ attitudes toward intercultural values after participating in the program. Additionally, selecting relevant literary materials and providing adequate teacher training are key factors in the successful implementation of this strategy. Therefore, this study recommends integrating literature-based literacy into children's educational curricula to foster a more inclusive and tolerant cultural understanding.